BETWEEN TRADITION AND CRITICISM: AN EPISTEMOLOGICAL ANALYSIS OF MUSTAFA AL-SIBĀʿĪ’S RESPONSE TO ORIENTALIST HADITH SCHOLARSHIP - Muhammad Ilyas; Abdullah Alifuddin Prasetyo; Nur Baiti Hidayah (EL-MAQRA', 2026)
This study examines the epistemological structure underlying Mustafa al-Sibāʿī’s critique of Orientalist Hadith scholarship. Previous studies tend to portray his approach as objective and balanced, yet they largely remain descriptive and fail to critically interrogate its epistemological foundations. This study addresses this gap by analyzing whether al-Sibāʿī’s critique constitutes a genuinely critical engagement or primarily a normative defense of the Hadith tradition. Employing a qualitative library-based method, this research integrates discourse analysis, content analysis, and comparative epistemological analysis. The study focuses on al-Sibāʿī’s major works and compares his arguments with key Orientalist scholars such as Ignaz Goldziher and Joseph Schacht, as well as with contemporary Muslim scholars like Mustafa al-Aʿẓamī. The findings reveal that al-Sibāʿī combines internal Hadith criticism with selective empirical reasoning; however, his framework remains rooted in a tradition-based epistemology that produces asymmetrical critique. This study argues that the debate between classical Hadith scholarship and Orientalism reflects a contest between distinct epistemological systems. The novelty of this research lies in providing a systematic epistemological evaluation of al-Sibāʿī’s critique beyond descriptive and apologetic approaches.